Enhancing Collaboration and Learning Through a Problem-Based Game in Lower Secondary Social Studies - Amalina Farida; Sriyanto Sriyanto; Seyithan Demirdag (International Journal of Social Learning (IJSL), 2025)
This study was motivated by the low collaboration skills and learning outcomes in social studies subjects, which are attributed to monotonous learning methods and the underutilization of digital learning media. The research aims to analyze the effectiveness of the "Journey to Merdeka" educational game integrated with the Problem-Based Learning (PBL) model in enhancing students’ collaboration skills and learning outcomes. Employing a mixed-method research and development (R&D) approach, this study involved 8th-grade students from three junior high schools in Brebes Regency. Key stages included product design, validation, testing, and analysis using statistical techniques such as Wilcoxon and N-gain tests. Findings show a significant increase in collaboration skills—students categorized as "very good" rose from 10.81% to 97.30%—and improved learning outcomes, with an N-gain score of 0.6213 (moderate effectiveness). The results confirm that the educational game is valid and well-received, and effective in supporting active learning, problem-solving, and collaborative engagement in social studies.